Perinuclear Localization of Internalized Outer Membrane Vesicles Carrying Active Cytolethal Distending Toxin from Aggregatibacter actinomycetemcomitans - Rompikuntal, Pramod Kumar (American Society for Microbiology, 2012)
Aggregatibacter actinomycetemcomitans is implicated in aggressive forms of periodontitis. Similarly to several other Gram-negative species, this organism produces and excretes a cytolethal distending toxin (CDT), a genotoxin associated with cell distention, G(2) cell cycle arrest, and/or apoptosis in many mammalian cell types. In this study, we have identified A. actinomycetemcomitans outer membrane vesicles (OMVs) as a vehicle for simultaneous delivery of multiple proteins, including CDT, into human cells. The OMV proteins were internalized in both HeLa cells and human gingival fibroblasts (HGF) via a mechanism of OMV fusion with lipid rafts in the plasma membrane. The active toxin unit, CdtB, was localized inside the nucleus of the intoxicated cells, whereas OmpA and proteins detected using an antibody specific to whole A. actinomycetemcomitans serotype a cells had a perinuclear distribution. In accordance with a tight association of CdtB with OMVs, vesicles isolated from A. actinomycetemcomitans strain D7SS (serotype a), in contrast to OMVs from a D7SS cdtABC mutant, induced a cytolethal distending effect on HeLa and HGF cells, indicating that OMV-associated CDT was biologically active. Association of CDT with OMVs was also observed in A. actinomycetemcomitans isolates belonging to serotypes b and c, indicating that OMV-mediated release of CDT may be conserved in A. actinomycetemcomitans. Although the role of A. actinomycetemcomitans OMVs in periodontal disease has not yet been elucidated, our present data suggest that OMVs could deliver biologically active CDT and additional virulence factors into susceptible cells of the periodontium.